Beta Decay Rates Evaluated Within the Gross Theory Using Experimental Data for the Gamow-Teller Resonance Parameter - Rocha de Azevedo, M. (2020)
We improve the results for the β⁻-decay rates obtained within the context of the Gross Theory of Beta Decay (GTBD) by using new values of the parameter σN related to the standard deviation for the Gamow-Teller resonance: we include experimental data when they are available and, if not, we adopt the value of the nearest neighbor previous (that is, with less mass) that has experimental data. We evaluate the β⁻-decay rates using a Gaussian energy distribution function with the axial-vector weak coupling constant |gA| = 1, considering updated experimental mass defects and also an improved approximation for the Fermi function. Our sample consists of 94 nuclei with mass in the range 46 < A < 70, all of them decaying by means of allowed transitions, which are of interest in the pre-supernova phase and have experimental data in terrestrial conditions available in the Letter of Nuclides. We compare our result with those obtained within the same GTBD but using values of σN adjusted in Possidonio (Braz. J. Phys. 48:485, 2018) by minimizing the χ²-function, and also with systematic microscopic calculations. We have shown that the substitution of the adjusted parameters by experimental data in GTBD improves the results for β⁻-decay rates by 6.4%.